On the riskiness of lower‐tier suppliers: Managing sustainability in supply networks - Villena, Verónica H.; Gioia, Dennis A. (Journal of Operations Management, 2018)
AbstractAlthough multinational companies (MNCs) have increasingly embraced a sustainability strategy for their own operations, fewer have tried to engage their (tier‐one) suppliers in their sustainability initiatives. It is even rarer that MNCs engage their suppliers' suppliers (lower‐tier suppliers), despite the latter having a higher incidence of violations with more acute environmental and social impacts that can jeopardize the MNCs’ operations and reputation. We conducted inductive research on three supply networks in the automotive, electronics, and consumer product/pharmaceutical industries. We collected data on three leading sustainable MNCs and a subset of 9 tier‐one suppliers and 22 lower‐tier suppliers and complemented that information with data on several NGOs and industry organizations. This study (1) reveals that many lower‐tier suppliers address their environmental and labor issues passively and constitute the riskiest suppliers in a supply network; (2) provides a grounded theoretical framework for managing a sustainable supply network that accounts for multiple network members as well as three sustainability dimensions (the 3Ps: profit, people, and planet); and (3) shows how processes MNCs use to manage their suppliers differ from processes these suppliers use with their own (lower‐tier) suppliers. The study reveals the practices that leading sustainable MNCs use to manage their supply networks and provides important future research directions.